AI-Assisted Preparation of Solanum melongena Leaf Extract for Mitigating Corrosion of Mild Steel in Acidic Environments - Okeke, Pamela Ifeoma; Okore, Glory Jerry; Adindu, Blessing Chinonso; Ehirim, Appolinus; Nwugha, Victor Ndubuisi; Nleonu, Emmanuel Chile; Okeke, Paulicarp Onyinyechi (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
Artificial Intelligence (AI) and Chemistry applications are mostly focused on preparation, characterization and applications of extracts of natural products in corrosion inhibition, wastewater treatment, biochemical systems, etc. Artificial intelligence can be useful in chemistry and allied field in the areas of compound manufacture and characterization. The present study explores the preparation and unique use of acid extract of Solanum melongena (SM) leaves commonly known as garden egg to truncate deterioration of mild steel in hydrochloric acid and tetraoxosulphate (VI) acid. Mild steel of dimensions 30 mm x 30 mm x 1.4 mm was used for the experiment. It was suspended in the corrodents: 1 mol/L hydrochloric acid and 0.5 mol/L tetraoxosulphate (VI) acid. Acid extract of SM was added as 0.4 g/L, 0.4 g/L and 1.6 g/L concentration, to investigate its effects against dissolution of mild steel by making use of mass loss and electrochemical techniques. The result showed that acid extract of SM effectively truncated the dissolution of mild steel in 1 mol/L of hydrochloric acid and 0.5 mol/L of tetraoxosulphate (VI). The result presented more effectiveness as the concentration increased with prolonged time. Mass loss was reduced more in the 1 M HCl system giving 96.65 % while the 0. 5 mol/L H2SO4 gave 95.85 % inhibitor efficacy, showing good effectiveness for both systems. Polarization experiments revealed a multi-faced character of inhibitor, reducing cathodic, as well as anodic current densities. Surface coverage data using Langmuir adsorption isotherm showed interaction among the adhered substances on the surface of the mild steel with increased surface coverage. The various processes of the preparation, characterization and applications of the leaf extracts are then assigned to AI for any possible relationship in carrying out the processes.